Evaluating Country Food in the Northern Native Economy - Usher, Peter J. (ARCTIC, 1976)
A means is sought of estimating the value of domestically-produced country food, which is of considerable importance in the northern native economy. The problems involved include the determination of the actual volume of production as well as the uses made of it, the evaluation of income in kind, particularly through the imputation of cash values, and the assessment of the intangibles involved in any direct comparison between the modern and traditional sectors of the northern economy. It is concluded that substitution costs provide the most appropriate measure of value and their use is, therefore, recommended, but with the caution that they cannot serve to measure the value of the activity or environment which produces the country food.